Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris - Shawn Larson; Roderick B. Gagne; Jim Bodkin; Michael J. Murray; Katherine Ralls; Lizabeth Bowen; Raphael Leblois; Sylvain Piry; Maria Cecilia Penedo; M. Tim Tinker; Holly B. Ernest (Marine Mammal Science, 2021)
Sea otters, Enhydra lutris , were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, population structure, and connectivity between remnant and reintroduced populations. Average genetic diversity within populations was similar: observed heterozygosity 0.55 and 0.53, expected heterozygosity 0.56 and 0.52, unbiased expected heterozygosity 0.57 and 0.52, for reintroduced and remnant populations, respectively. Sea otter population structure was greatest between the Northern and Southern sea otters with further structuring in Northern sea otters into Western, Central, and Southeast populations (including the reintroduced populations). Migrant analyses suggest the successful reintroductions and growth of remnant groups have enhanced connectivity and gene flow between populations throughout many of the sampled Northern populations. We recommend that future management actions for the Southern sea otter focus on future reintroductions to fill the gap between the California and Washington populations ultimately restoring gene flow to the isolated California population.